REPRESENTASI BUDAYA TIONGHOA DALAM PENGEMBANGAN PARIWISATA DI KAWASAN SURYA KENCANA KOTA BOGOR - Renaldi; Darmawan, Fahrurozy; Rusli, Meizar (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study aims to analyze the representation of Chinese culture in the tourism development of the Surya Kencana area in Bogor City, which holds significant potential as a cultural tourism destination. A qualitative approach was employed, utilizing SWOT analysis as the methodological framework. Data were collected through structured interviews with key informants, including representatives from the Bogor City Tourism and Culture Office, Chinese cultural figures, local residents, and visitors, as well as through direct field observations. The theory of representation was used to examine elements of material culture, performing arts, and cultural festivals. The findings reveal that Chinese culture is represented through architectural features, traditional culinary practices, performing arts such as Barongsai and Liong, and cultural festivals such as Cap Go Meh. The SWOT analysis produced an Internal Factor Evaluation (IFE) score of 0.98 and an External Factor Evaluation (EFE) score of 0.8, underscoring the importance of adaptive strategies in the development of culture-based tourism. Despite its potential, the area still faces development challenges, particularly limited promotion and low public awareness. This study recommends the strategic use of digital technology, improved promotional efforts, and active community collaboration as essential measures to preserve and further develop Chinese cultural heritage in the Surya Kencana area.